Analyzing In Silico the Relationship Between the Activation of the Edema Factor and Its Interaction With Calmodulin - Pitard, Irène; Monet, Damien; Goossens, Pierre L.; Blondel, Arnaud; Malliavin, Thérèse E. (Frontiers in Molecular Biosciences, 2020)
Molecular dynamics (MD) simulations have been recorded on the complex between the edema factor (EF) of {\it Bacilllus anthracis} and calmodulin (CaM), starting from a structure with the orthosteric inhibitor adefovir bound in the EF catalytic site. The starting structure has been destabilized by alternately suppressing different co-factors, such as adefovir ligand or ions, revealing several long-distance correlations between the conformation of CaM, the geometry of the CaM/EF interface, the enzymatic site and the overall organization of the complex. An allosteric communication between CaM/EF interface and the EF catalytic site, highlighted by these correlations, was confirmed by several bioinformatics approaches from the literature. A network of hydrogen bonds and stacking interactions extending from the helix V of CaM, and the residues of the switches A, B and C, and connecting to catalytic site residues, is a plausible candidate for the mediation of allosteric communication. The greatest variability in volume between the different MD conditions were also found for cavities present at the EF/CaM interface and in the EF catalytic site. The similarity between the predictions from literature and the volume variability might introduce the volume variability as new descriptor of allostery.